Pancreatic Solid Pseudopapillary Neoplasms in Childhood - Vedder, Katharina; Vassilev, Georgi; Şandra-Petrescu, Flavius Ionuţ; Abdelhadi, Schaima; Hermann, Maike; Reißfelder, Christoph (Pancreas, 2025)
An abstract is unavailable.
Gesehen am 26.05.2025